Peculiarities in the lower extremity amputation and prosthetics in children - Khobotov, Sergey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
In this work its author elucidates surgical peculiarities of the lower extremity amputation in children with consideration of its necessity, as well as key aspects of prosthetics for children, including preparation of a stump, prosthetic design requirements and training in using prostheses by children and their parents.